Galaxy protocluster candidates at 1.6< z?2 - Galametz, A.; Vernet, J.; De Breuck, C.; Hatch, N.; Miley, G.; Kodama, T.; Kurk, J.; Overzier, R.; Rettura, A.; Röttgering, H.; Seymour, Nick; Venemans, B.; et al. (EDP Sciences, 2010)
We present a study of protoclusters associated with high redshift radio galaxies. We imaged MRC 1017-220 (z = 1.77) and MRC 0156-252 (z = 2.02) using the near-infrared wide-field (7.5' × 7.5') imager VLT/HAWK-I in the Y, H, and Ks> bands. We present the first deep Y-band galaxy number counts within a large area (~200 arcmin2). We develop a purely near-infrared colour selection technique to isolate galaxies at 1.6 < z < 3 that may be associated with the two targets, dividing them into (i) red passively evolving or dusty star forming galaxies or (ii) blue/star formation dominated galaxies with little or no dust. Both targeted fields show an excess of star forming galaxies with respect to control fields. No clear overdensity of red galaxies is detected in the surroundings of MRC 1017-220 although the spatial distribution of the red galaxies resembles a filament-like structure within which the radio galaxy is embedded. In contrast, a significant overdensity of red galaxies is detected in the field of MRC 0156-252, ranging from a factor of ~2-3 times the field density at large scales (2.5 Mpc, angular distance) up to a factor of ~3-4 times the field density within a 1 Mpc radius of the radio galaxy. Half of these red galaxies have colours consistent with red sequence models at z ~ 2, with a large fraction being bright (Ks < 21.5, i.e. massive). In addition, we also find three galaxies within 5" of MRC 0156-252 suggesting that the radio galaxy has multiple companions within ~50 kpc. We conclude that the field of MRC0156-252 shows many remarkable similarities with the well-studied protocluster surrounding PKS1138-262 (z = 2.16) suggesting that MRC 0156-252 is associated with a galaxy protocluster at z ~ 2. © 2010 ESO.